An evolutionary-based methodology for symbolic simplification of analog circuits using genetic algorithm and simulated annealing. Issue 3 (15th February 2015) - Shokouhifar, Mohammad; Jalali, Ali
Highlights An evolutionary-based multi-objective methodology is proposed for automatic symbolic simplification of analog circuits. The simplified symbolic expressions are generated in MATLAB automatically from the input netlist of the circuit. A hybrid algorithm based on genetic algorithm and simulated annealing is used to test the proposed simplification criterion. The proposed algorithm is successfully tested on three analog circuits, and its results are compared with HSPICE.